Quality of life assessment of oncologically treated patients because of breast cancer - Aleksandra Trybulec; Filip Georgiew; Katarzyna Borowiec-Trybulec (University of Applied Sciences in Tarnow, Poland, 2022)
Introduction: Currently, in the world, breast cancer is recognized as one in four malignant neoplasms in women. It is the second most common cause of death in cancer patients. The disease, which is a threat to women's lives, leads to the loss of personal control, during its duration it becomes everyday life with negative emotions such as uncertainty, anxiety and anxiety. Women have contact with a range of negative effects that the disease provides, causing them to resign and destructive to the psychophysical sphere. Disorders in the physical and mental aspect of body image, side effects of therapy, sexual relations with a partner and anxiety about health in the future are factors that have a huge impact on the quality of life of patients. The aim of the study was to assess the quality of life of women with breast cancer. Materials and methods: The quality of life of 40 women with breast cancer who underwent oncological treatment was assessed using the author's questionnaire with 12 questions and QLQ-BR23 questionnaire with 23 questions. Results and conclusions: Studies have shown that the biggest problem for women was the side effects of the treatment and the most common discomfort during radiation therapy. They are characterized by redness of the skin, general weakness and fatigue, which in turn later translated into, a change in the perception of their body image, a decrease in their attractiveness, a sense of comfort and confidence. The obtained results showed that the lowest quality of life of the respondents was registered in the domain determining future perspectives. The best result was recorded in the domain of sexual pleasure and sexual functioning. When assessing the quality of life of the respondents, it follows that patients with vocational education have a worse quality of life within the domain of breast symptoms. Employed persons surveyed obtained worse quality of life results in terms of sexual functioning and sexual pleasure. Considering the duration of illness of the respondents, there were no statistically significant differences affecting the quality of life.